Marketing Research / A Problem Solving Approach - Blair Edward; Sudman Seymour (Mcgraw Hill Book Company, 1998)
Preface, An Overview of Marketing Research, Sources of Market Research Data, Tools for Primary Data Collection, Analyzing Data, Issues in Research Management, Glossary, Index.
Preface, An Overview of Marketing Research, Sources of Market Research Data, Tools for Primary Data Collection, Analyzing Data, Issues in Research Management, Glossary, Index.